The Improvement of Natural Thai Bentonite Modified with Cationic Surfactants on Hexavalent Chromium Adsorption from an Aqueous Solution - Nikom Srikacha; Manop Sriuttha; Lamyai Neeratanaphan; Chatree Saiyasombat; Bundit Tengjaroensakul (Adsorption Science & Technology)
This work was performed to evaluate the adsorption properties of modified Thai bentonites (MTBs) on hexavalent chromium (Cr(VI)) by using a popularly capable surfactant (hexadecyltrimethylammonium bromide (HDTMA)) compared to an alternative surfactant (cetylpyridinium chloride (CPC)). The adsorption properties of the surfactant load, adsorbent weight, contact time, initial Cr(VI) concentration, and temperature of the MTBs were evaluated. The results revealed that a higher surfactant load significantly affected the Cr(VI) adsorption, and the equilibrium adsorption was achieved at 60 min. The adsorption capacity improved when the adsorbent weight, contact time, initial concentration, and temperature increased as the highest adsorption capacities of 1CPC and 1HDTMA were 45.55 and 46.03 mg g-1, respectively. The isotherm and kinetic adsorptions were described by the Freundlich model and pseudo-second-order model, respectively, while thermodynamics indicated endothermic adsorption. After adsorption, X-ray absorption near-edge structure and extended X-ray absorption fine structure data showed that Cr ions did not change the valency state between Cr(VI) and Cr(III). Additionally, the adsorption mechanism can be depicted as the ion exchange between the Cr(VI) ion and the surfactant molecule. Structural evaluations by XRD, FTIR, FESEM, EDS, and TEM found that both MTBs (1CPC and 1HDTMA) with the best adsorption performance for Cr(VI) had obvious changes at both the interlayer structure and the external surface. The interlayer spacing was expanded from 14.85 Å to 20.48 Å (1CPC) and 18.79 Å (1HDTMA), and the new functional groups (CH2 scissoring, C–H symmetric stretching, C–H asymmetric stretching, and N–CH3 scissoring) and elemental compositions (Br and Cl) were observed in both MTBs. They demonstrated that the complete intercalation of surfactant molecules on bentonite structures supported Cr(VI) adsorption. Overall, the data indicate that MTBs were perfectly adsorbed on Cr(VI), and CPC was demonstrated to be a cheap alternative agent due to its adsorption capacity compared to the popularly capable HDTMA.